Anti-NMDA Receptor Encephalitis Associated With an Ovarian Teratoma Presenting as First-episode Psychosis: A Case Report. Issue 1 (January 2022) - Câmara-Pestana, Pedro; Magalhães, Andreia D.; Mendes, Tiago; Levy, Pedro; Coentre, Ricardo
Abstract : We report an unusual case of a 27-year-old previously healthy female who presented with a 15-day history of psychotic, cognitive, and unspecified somatic symptoms. She was admitted to the psychiatric ward of an early intervention in psychosis team and medicated with aripiprazole. The young age of onset, the rapid onset, the absent history of psychiatric disease, and the persistence of a marked memory deficit after the psychotic symptoms remitted strongly suggested a nonpsychiatric etiology and led us to hypothesize autoimmune encephalitis as the most probable diagnosis. An investigation was carried out for anti-N-methyl-D-aspartate (anti-NMDA) receptor antibodies in the patient's serum and cerebrospinal fluid, and both tests were positive. The patient was transferred to the neurology ward, where an endovaginal ultrasound showed an ovarian teratoma in her right ovary. She underwent laparoscopic surgery without complications. She was initially treated with intravenous immunoglobulin and methylprednisolone for 5 days, which resulted in marked improvement of her memory and attention performance. Anti-NMDA receptor encephalitis, first described in 2007 by Dalmau and colleagues, is a form of auto-immune encephalitis with prominent neuropsychiatric manifestations, particularly psychotic symptoms. At symptom onset, distinguishing the disease from a primary psychiatric disorder is challenging. This case report highlights the importance of early psychosis treatment teams considering the diagnosis of anti-NMDA receptor encephalitis when evaluating new referrals with a potential diagnosis of first-episode psychosis, particularly when young patients with no relevant personal or familial psychiatric history present with neuropsychiatric symptoms and a distinctive pattern of symptom fluctuation over time.